Answer:
x = -
, x = 
Step-by-step explanation:
to find the points of intersection equate the 2 equations , that is
7x - 15 = 10 + 12x - 6x² ( subtract 10 + 12x - 6x² from both sides )
6x² - 5x - 25 = 0 ← factor the quadratic on left side
consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term
product = 6 × - 25 = - 150 and sum = - 5
the factors are - 15 and + 10
use these factors to split the x- term
6x² - 15x + 10x - 25 = 0 ( factor the first/second and third/fourth terms )
3x(2x - 5) + 5(2x - 5) = 0 ← factor out (2x - 5) from each term
(2x - 5)(3x + 5) = 0
equate each factor to zero and solve for x
3x + 5 = 0 ⇒ 3x = - 5 ⇒ x = - 
2x - 5 = 0 ⇒ 2x = 5 ⇒ x = 
- 5x.
In case you actually want to know how I got it:
the question is just saying "8x - 13x".
8 - 13 = -5
Answer:
4
Step-by-step explanation:
T(n) = n² + 3
T(1) = 1² + 3 = 1 + 3 = 4
Answer:
5.16
Step-by-step explanation:
Since after x=3, value of y starts decreasing for increasing values of x, let's choose. Also we need to find f(x) for x=3.4
x=3,4,5 and f(x)=7,3,1 to find lagrange polynomial
P(x)= ((x-x2)(x-x3)y1)/((x1-x2)(x1-x3) + ((x-x1)(x-x3)y2)/((x2-x1)(x2-x3) + ((x-x1)(x-x2)y3)/((x3-x1)(x3-x2)
P(x)= ((x-4)(x-5)7)/((3-4)(3-5)) + ((x-3)(x-5)3)/((4-3)(4-5)) + ((x-3)(x-4)1)/((5-3)(5-4))
P(x)= x² -11x+31
P(3.4)= 5.16